Create and Craft: Understanding the Lived Experience of Education Program Supervisors in Leading the Implementation of Contextualized Learning Resources - Montillano, Allen Cris; Yango, Antonio (Technium Social Sciences Journal, 2024)
In the years of the contextualization of the learning materials, it has been studied that these are effective in the improvement of the quality of teaching and learning experiences. In the Philippine public school system, education program supervisors play a pivotal role in leading the implementation of contextualized learning resources by ensuring that instructional materials are tailored to meet the diverse needs and backgrounds of students. They work closely with educators to develop and adapt curricula that reflect the cultural, social, and linguistic contexts of the learners, thereby making education more relevant and engaging. The researchers utilized the phenomenological research design to understand and describe the lived experience of Education Program Supervisors in leading the implementation of contextualized learning resources. Data were gathered through semi-structured one-on-one interviews with randomly selected education program supervisors, and results were interpreted through thematic analysis The salient findings of the study are: (1) education program supervisors underscore their crucial role in implementing contextualized learning materials to improve engagement and relevance, emphasizing the importance of quality assurance in ensuring accuracy, accessibility, and effectiveness through thorough evaluation and monitoring, while also acknowledging the significance of leadership in fostering learning resources to enhance students' application of knowledge to real-world scenarios and overall educational quality and (2) they are using transformational leadership, efficient workload management, and a collaborative approach to address challenges in implementing contextualized learning resources, aiming to improve educational outcomes for both teachers and students.